Guide to the literaty analysis for senior students in high school - Guerra, Karen; Quintero, Iris; Quintero, Lourdes (David, Panamá : UDELAS, 2011)
During the development of this project, we have focused in needs, interests and skills of the students through a series of interesting aand fun activities such as role play, cause and effect game, comprehension spinner, persuasion activity and others in order to motivate them to interact with each other and literature readings.
GENERAL INDEX TITLE PAGE QUOTACION PROVERB DEDICATION ACKNOPWLEDGMENT GENERAL INDEX CHART INDEX GRAPHIC INDEX ANNEX INDEX INTRODUCTION CHAPTER I: THE PROBLEM OF THE INVESTIGATION CHAPTER II: THEORETICAL FRAMEWORK 2.1. Theoretical bacground 2.1.1. North american literature 2.1.2. The age of the naturalism 2.1.3. Characteristics of the age of the naturalism 2.1.4. Influence of the age of the naturalism 2.1.5. Authors of the age of the naturalism 2.1.6. Life 2.2. Steps for literary analysis applied in the development of english classes 2.2.1. Introduction 2.2.2. Content 2.2.3.Structure 2.2.4. Form and stuyle 2.2.5. Genre 2.2.6. Theme And others more CHAPTER 3: DATA COLLECTION AND ANALYSIS CHAPTER 4: ANALYSIS OF THE RESULTS CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEXES
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; COLLEGE OF SOCIAL AND SPECIAL EDUCATION; BACHELOR DEGREE IN ENGLISH TEACHING; LICENCIATURA EN DOCENCIA EN INGLES